Cerebral vascular function following the acute consumption of caffeinated artificially- and sugar sweetened soft drinks in healthy adults - Reed, Emma L.; Worley, Morgan L.; Kueck, Paul J.; Pietrafasa, Leonard D.; Schlader, Zachary J.; Johnson, Blair D. (Frontiers in Human Neuroscience, 2022)
Chronic consumption of sugar- and artificially-sweetened beverages (SSB and ASB) are associated with an increased risk of stroke but it is unclear how acute consumption influences cerebral vascular function. Purpose: We hypothesized that: (1) acute consumption of SSB and ASB would augment dynamic cerebral autoregulation (dCA) and attenuate cerebral vascular reactivity to hypercapnia (CVRCO2) compared to water; and (2) dCA and CVRCO2 would be attenuated with SSB compared to ASB and water. Methods: Twelve healthy adults (age: 23 ± 2 years, four females) completed three randomized trials where they drank 500 ml of water, SSB (Mountain Dew®), or ASB (Diet Mountain Dew®). We measured mean arterial pressure (MAP), middle and posterior cerebral artery blood velocities (MCAv and PCAv), and end-tidal CO2 tension (PETCO2). Cerebral vascular conductance was calculated as cerebral artery blood velocity/MAP (MCAc and PCAc). Twenty min after consumption, participants completed a 5 min baseline, and in a counterbalanced order, a CVRCO2 test (3%, 5%, and 7% CO2 in 3 min stages) and a dCA test (squat-stand tests at 0.10 Hz and 0.05 Hz for 5 min each) separated by 10 min. CVRCO2 was calculated as the slope of the linear regression lines of MCAv and PCAv vs. PETCO2. dCA was assessed in the MCA using transfer function analysis. Coherence, gain, and phase were determined in the low frequency (LF; 0.07–0.2 Hz) and very low frequency (VLF; 0.02–0.07 Hz). Results: MCAv and MCAc were lower after SSB (54.11 ± 12.28 cm/s, 0.58 ± 0.15 cm/s/mmHg) and ASB (51.07 ± 9.35 cm/s, 0.52 ± 1.0 cm/s/mmHg) vs. water (62.73 ± 12.96 cm/s, 0.67 ± 0.11 cm/s/mmHg; all P < 0.035), respectively. PCAc was also lower with the ASB compared to water (P = 0.007). MCA CVRCO2 was lower following ASB (1.55 ± 0.38 cm/s/mmHg) vs. water (2.00 ± 0.57 cm/s/mmHg; P = 0.011) but not after SSB (1.90 ± 0.67 cm/s/mmHg; P = 0.593). PCA CVRCO2 did not differ between beverages (P > 0.853). There were no differences between beverages for coherence (P ≥ 0.295), gain (P ≥ 0.058), or phase (P ≥ 0.084) for either frequency. Discussion: Acute consumption of caffeinated SSB and ASB resulted in lower intracranial artery blood velocity and conductance but had a minimal effect on cerebral vascular function as only MCA CVRCO2 was altered with the ASB compared to water.